STUDENTS ACTIVE ROLE IN LEARNING THE BASICS OF ANALYTICAL CHEMISTRY IN OCCUPATIONAL HEALTH, SAFETY AND ENVIRONMENT SUBJECT BY USING THE DISCOVER LEARNING MODEL - Wati, Erna; Tri Wahyuni Maharani, Endang (Education, Science, and Technology International Conference, 2025)
The study uses the classroom action research method carried out in two cycles. The research aims to improve the learning outcomes of Occupational Safety and Environmental Health subject for SMK Negeri 1 Temanggung students grade 10 of academic year 2023/2024. Whereas at the time of the pre-research, 21 students were declared failed and 15 students were declared passed at the minimum passing grade of 75. Research result shows that there are significant improvements on the learning outcome after applying the Discovery Learning Model. Analysis on the passing grade result before the research begins is 90% or 1 student declared passed. Result of the first cycle, the passing grade is 72% or 26 students declared passed, and on the second cycle the passing grade is 86% or 31 students declared passed. The conclusion of this study is that the use of the Discovery Learning Model can improve the learning outcomes of Occupational Safety and Environmental Health subject in Grade 10 students of Analytical Chemistry 3 of SMK Negeri 1 Temanggung for the 2023/2024 Academic Year.